More complications in cervical than in non-cervical spine tuberculosis. Issue 3 (3rd March 2020) - Pourbaix, Annabelle; Zarrouk, Virginie; Allaham, Wassim; Leflon, Véronique; Rousseau, Marc-Antoine; Goutagny, Stephane; Guigui, Pierre; Fantin, Bruno
Abstract: Purpose: Cervical spine tuberculosis (CST) is a rare disease that may lead to severe neurological complications. The goal of the study was to compare the characteristics of patients with CST with those of patients with non-cervical spine tuberculosis (NCST). Methods: Between 1997 and 2016, we reviewed all cases of proven tuberculosis from a cohort of spine infections in a tertiary care hospital. Clinical, biological, and imaging data were collected at baseline and after treatment. Results: Fifty-one cases of spine tuberculosis were included: 14 with CST on imaging (27%) and 37 with no cervical localization. Median age was 39 y. Demographic characteristics, duration of symptoms and neurological findings of spine compression were similarly present at presentation in CST and NCST patients. On imaging, lesions were more often multifocal in CST than in NCST patients (9/14 [64%] versus 10/37 [27%], p  = .014). Spinal surgery was required in 32/51 (63%) patients. At the end of follow-up (median: 20 months), cure rates were similar in CST and NCST patients but motor and/or sensitive functional sequel were more frequent in CST than NCST patients (6/14 [43%] versus 2/37 [5%], p  = .003). Conclusions: Cervical involvement is present in more than a quarter of patients with spinal tuberculosis. Patients with CST had more frequent neurological sequelae than patients with NCST. This was mainly due to a more multifocal disease at presentation. Screening for cervical localization should be systematic in patients with spinal tuberculosis even in the absence of cervical symptoms.